Acute Parkinsonism in Young Adult Following Streptococcal Infection (Bangladesh Journal of Infectious Diseases, 2021)
Acute parkinsonism following streptococcal infection is rarely reported. To date, there is paucity of literature of post streptococcal immune mediated acute parkinsonism and dyskinesia among adult. We report a case of 18 years old woman, who presented with acute parkinsonism after streptococcal tonsillitis. The patient who was previously well presented with a two-month history of intermittent fever, associated with sore throat and sudden onset of behaviour changes. She has been found to be quieter and respond slowly to questions and commands in the preceding one week prior to admission. Features of secondary parkinsonism was noted during examination. Her blood counts, viral screenings and anti-NMDAR were unremarkable. Her lumbar puncture revealed an opening pressure of 10 cm CSF with normal constituents. The ASO titre was raised up to 400IU/ml. Electroencephalogram (EEG) shows mild encephalopathy changes and MRI brain shows normal finding. She was initially treated initially for meningoencephalitis with intravenous acyclovir 500mg q8h and ceftriaxone 2g q12h, concomitant with intravenous methylprednisolone 1g daily for 3 days. Intravenous immunoglobulin was started on her in view of poor response to the above treatment, which later resulted in significant and rapid clinical improvement. Upon clinic review at 3 months, her tremor, bradykinesia, and rigidity resolved. Her medication was able to be weaned off and she was referred to the ENT team for further evaluation for tonsillectomy. This case illustrates the importance of recognising post-streptococcal infection as aetiology of acute parkinsonism in young adults, to avoid treatment delay. As illustrated in our case, the prognosis was excellent with prompt immunomodulatory therapy.Bangladesh Journal of Infectious Diseases 2020;7(2):110-112